Introduction to communication networks - Anttalainen, Tarmo; Jaaskelainen, Ville (Artech House, 2014)
This new book is an introduction to modern communications networks that now rely far less on telephone services and more on cellular and IP networks. The resource is designed to provide answers to the fundamental questions concerning tele--communications networks and services